Deafness Weakens Interareal Couplings in the Auditory Cortex - Yusuf, Prasandhya Astagiri; Hubka, Peter; Tillein, Jochen; Vinck, Martin; Kral, Andrej (Frontiers in Neuroscience, 2021)
The function of the cerebral cortex essentially depends on the ability to form functional assemblies across different cortical areas serving different functions. Here we investigated how developmental hearing experience affects functional and effective interareal connectivity in the auditory cortex. An animal model with years-long and complete auditory deprivation (deafness) from birth, the congenitally deaf cat (CDC), has been used. Using intracortical multielectrode arrays neuronal activity of adult hearing controls and congenitally deaf cats was registered in the primary auditory cortex and the secondary posterior auditory field (PAF). Ongoing activity as well as responses to acoustic stimulation (in adult hearing controls) and electric stimulation via cochlear implants (in adult hearing controls and CDCs) were analyzed. As functional connectivity measures pairwise phase consistency and Granger causality were used. While the number of coupled sites was nearly identical between controls and CDCs, a reduced coupling strength between the primary and the higher order field was found in CDCs under auditory stimulation. Such stimulus-related decoupling was particularly pronounced in the alpha band and in top-down direction. Ongoing connectivity did not show such a decoupling. These findings suggest that developmental experience is essential for functional interareal top-down interactions during sensory processing. The outcomes demonstrate that corticocortical couplings, particularly top-down cortical processing, are compromised following congenital sensory deprivation.